The Design of Vacuum Frying for Making Rambutan Chips - Susilawati Susilawati; Azhis Sholeh Buchori; Oyok Yudiyanto; Faadiyah Cheryl Rachelia (Universitas Sultan Ageng Tirtayasa, 2024)
Vacuum Frying is a tool used to process raw materials into chips using a vacuum system. Basically, food ingredients will be fried at a temperature below the boiling temperature of the oil, so that the water content in the food ingredients will evaporate. The aim of research is to create design and development of vacuum frying with thermo control. Vacuum functions to reduce the pressure in the frying chamber, so that the oil will boil below the boiling temperature of the oil, namely below 3000 to avoid burning by evaporating the water content (vacuumed) and minimizing the content lost by the heat of the oil. The design of the research consists of collecting data, design process, manufacturing process, machine testing, and evaluation. The oil tank capacity is 80 liters while the frying capacity reaches 10 kg. The vacuum frying process begins by putting oil into the drum and then heating the oil. Next, the raw materials are put into the chamber, after the oil boils, the vacuum faucet is turned on by turning it. Then the pump is turned on and the chamber is rotated to process the raw material into chips. According to the machine testing 1.5 kg of rambutan chips were produced from 3.1 kg of raw materials and 1.3 kg of banana chips were produced from 3.9 kg of raw materials. Both trials were carried out for 1 hour 20 minutes. For the temperature from the test results, the initial temperature was 60°C and during testing the highest temperature reached 80°C.